PELATIHAN TEKNIK BUDIDAYA IKAN DI MADRASAH ALIYAH HASYIM ASY’ARI BANGSRI JEPARA - Arif Mustofa; Budi Aryono; Noor Hamid (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Community service based on the development of the target schools at MA Hasyim Asyari Bangsri Jepara is intended as an effort to improve learning management in partner schools. The purpose of this community service program is to build academic cooperation, develop human resource potential and improve the quality of school education through skill program innovation. The training was held in two stages, namely the theory-discussion stage and the field stage. The participants of this training were teachers, assistant teachers, and students. The class training materials are the rules of fish farming, getting to know the tools and functions of the equipment, knowing how to design aquaculture containers, the sequence of cultivation activities, caring for and feeding and monitoring fish health. While the field training includes the design of aquaculture pond containers to fish farming techniques. The result of the activity was the implementation of community service activities for the development of the target schools in the form of training on catfish cultivation techniques for students and teachers of MA Hasyim Asyari Bangsri. The training participants understand cultivation techniques, starting from preparing cultivation media, spreading seeds, managing feed and maintaining water quality so that the fish grow well.